2014
DOI: 10.1016/j.schres.2013.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Brain structure in different psychosis risk groups in the Northern Finland 1986 Birth Cohort

Abstract: We tested the hypothesis that family risk for psychosis (FR) and clinical risk for psychosis (CR) are associated with structural brain abnormalities, with increased deficits in those at both family risk and clinical risk for psychosis (FRCR). The study setting was the Oulu Brain and Mind Study, with subjects drawn from the Northern Finland 1986 Birth Cohort (n=9479) using register and questionnaire based screening, and interviews using the Structured Interview for Prodromal Symptoms. After this procedure, 172… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Reduced grey matter volume across the cerebellum has been reported in patients with in schizophrenia [140, 141], although there is also a report of increased vermis volume in individuals with positive psychotic symptoms and thought disorder [142]. Reduced rsFC is found between bilateral cerebellar lobules IV and V and the dorsal attention network [143], and between cerebellum and thalamus [144].…”
Section: The Cerebellum In Social Cognition and Affective Processingmentioning
confidence: 99%
“…Reduced grey matter volume across the cerebellum has been reported in patients with in schizophrenia [140, 141], although there is also a report of increased vermis volume in individuals with positive psychotic symptoms and thought disorder [142]. Reduced rsFC is found between bilateral cerebellar lobules IV and V and the dorsal attention network [143], and between cerebellum and thalamus [144].…”
Section: The Cerebellum In Social Cognition and Affective Processingmentioning
confidence: 99%
“…In our earlier MRI study with this same sample we did not find any structural changes or disruptions in white matter integrity (Roman-Urrestarazu et al, 2014;Koivukangas et al, manuscript). It is suggested that structural changes with FR may occur later during the onset process of psychosis (Pantelis et al, 2003).…”
Section: Discussionmentioning
confidence: 51%
“…Interestingly, Joyal et al (2004) also reported selective reductions in the inferior vermis in 19 SCZ patients compared to 19 HC whereas Segarra et al (2008) found a reduction in the total gray matter volume of the cerebellar vermis in adult patients compared to age-and gender-matched HC, respectively. Notably, cerebellar deficits have also been observed in subjects at psychotic risk in a study carried out by (Roman-Urrestarazu et al, 2014). Indeed, the authors highlighted a cluster of lower gray matter at the cerebellar vermis level, in patients with both clinical and familiar risk of psychosis (Roman-Urrestarazu et al, 2014) .…”
Section: Resultsmentioning
confidence: 92%